Reclaiming Political Urbanism in Peace Building Processes: The Hands-on Famagusta project, Cyprus - Socrates Stratis; Emre Akbil (Footprint, 2017)
This case study is about reclaiming a political form of urbanism before the potential Cyprus reunification by enhancing, through the Hands-on Famagusta project, ‘agonistic’ collective practices across the Cypriot divide.